Advances in the Synthesis and Application of Magnetic Ferrite Nanoparticles for Cancer Therapy - Seipati Rosemary Mokhosi; Wendy Mdlalose; Amos Nhlapo; Moganavelli Singh (MDPI AG, 2022)
Cancer is among the leading causes of mortality globally, with nearly 10 million deaths in 2020. The emergence of nanotechnology has revolutionised treatment strategies in medicine, with rigorous research focusing on designing multi-functional nanoparticles (NPs) that are biocompatible, non-toxic, and target-specific. Iron-oxide-based NPs have been successfully employed in theranostics as imaging agents and drug delivery vehicles for anti-cancer treatment. Substituted iron-oxides (MFe2O4) have emerged as potential nanocarriers due to their unique and attractive properties such as size and magnetic tunability, ease of synthesis, and manipulatable properties. Current research explores their potential use in hyperthermia and as drug delivery vehicles for cancer therapy. Significantly, there are considerations in applying iron-oxide-based NPs for enhanced biocompatibility, biodegradability, colloidal stability, lowered toxicity, and more efficient and targeted delivery. This review covers iron-oxide-based NPs in cancer therapy, focusing on recent research advances in the use of ferrites. Methods for the synthesis of cubic spinel ferrites and the requirements for their considerations as potential nanocarriers in cancer therapy are discussed. The review highlights surface modifications, where functionalisation with specific biomolecules can deliver better efficiency. Finally, the challenges and solutions for the use of ferrites in cancer therapy are summarised.